2017
DOI: 10.2471/blt.16.170167
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study of socioeconomic support to enhance tuberculosis prevention and treatment, Peru

Abstract: ObjectiveTo evaluate the impact of socioeconomic support on tuberculosis preventive therapy initiation in household contacts of tuberculosis patients and on treatment success in patients.MethodsA non-blinded, household-randomized, controlled study was performed between February 2014 and June 2015 in 32 shanty towns in Peru. It included patients being treated for tuberculosis and their household contacts. Households were randomly assigned to either the standard of care provided by Peru’s national tuberculosis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 36 publications
4
112
0
4
Order By: Relevance
“…Our results are consistent with those of previous studies, [10][11][12] which investigated the effect of incentives as a method of social protection on the outcomes of tuberculosis treatment in lowincome countries. A study in Nigeria 10 showed that patients with tuberculosis who received $15 per month during treatment had a success rate that was approximately 15% higher than those who did not receive the incentive (p=0•003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with those of previous studies, [10][11][12] which investigated the effect of incentives as a method of social protection on the outcomes of tuberculosis treatment in lowincome countries. A study in Nigeria 10 showed that patients with tuberculosis who received $15 per month during treatment had a success rate that was approximately 15% higher than those who did not receive the incentive (p=0•003).…”
Section: Discussionsupporting
confidence: 92%
“…9 What is less clear is how best to implement social protection within the context of tuberculosis programmes to maximise the social, eco nomic, and public health impact for susceptible patients. 8 Although several studies from Nigeria, 10 Moldova, 11 and Peru 12 have shown that financial incentives are effective in improving treatment success among patients with tuberculosis, the generalisability and use of social protection interventions is context dependent.…”
Section: Effect Of the Bolsa Familia Programme On The Outcome Of Tubementioning
confidence: 99%
“…Accordingly, our findings, which suggest that mobile phone interventions relying on patient mobile phone access may relatively neglect such vulnerable groups and therefore potentially widen the inequality gap, have important implications for public health practitioners and TB policy makers as they design and scale‐up interventions. Specifically, mobile phone interventions that aim to deliver social protection schemes to patients with TB, such as cash transfers, should ensure patients have access to mobile phones to avoid inadvertently neglecting the very patients that they are most designed to help .…”
Section: Discussionmentioning
confidence: 99%
“…As part of the PREVENT TB study [9,10], our research group is evaluating a policy of risk-based preventive treatment for contacts in Peru, whereby all children aged <15 years are recommended to take preventive treatment, irrespective of TST results, and adults are informed of their risk using the IFHAD score. We aim to substantially increase uptake of preventive treatment among contacts and, through doing so, demonstrate that simple policies can be effectively delivered in primary care to prevent tuberculosis in people at high risk.…”
Section: To the Editormentioning
confidence: 99%